Transitional Justice as a Transformation Process towards Peace - Bolaños Enríquez, Tania Gicela (2019)
This article constitutes a contribution to the processes of peace consolidation developed during post-conflict scenarios. In this vein it proposes a path that allows to truly materialize the transformative effect of integral reparations, in particular in traditionally unequal societies, where victims of serious violations of human rights usually are members of the most marginalized and vulnerable groups. It starts from the idea that transitional justice is a process of political, social and cultural transformation, so that the reparation of that sort of violations must be designed and developed in such a way that it contributes to the transformation, avoiding being itself a generatorof new social gaps. Therefore, the classic approach of reparation measures, based on pure corrective justice, must give way to the need to change the structural causes of the conflict and open the way for a transformative reparation founded on a concept of social and distributive justice.